(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of the research was to find the incidence of hypertension in the patients visiting Medical OPD at B.V.H, Bahawalpur. Study Design: Observational / descriptive / cross sectional study. Place and Duration of Study: This study was conducted at Medical OPD, B.V.H, and Bahawalpur from 05 January 2016 to 05 April 2016. Materials and Methods: The data was collected through a pre-formed questionnaire about knowledge of patients regarding hypertension. Data was entered and analyzed using SPSS 17. All result was presented in percentages, frequencies, and tables. Results: Three hundred and thirty-two patients were examined during the study period with the age of 20 to 60 and above years. Among the study sample, 147(44%) were males and 185(56%) females. Maximum hypertensive patients 54(16.3%) were found among the age group of 41-50 years. Hypertension was found to be present in 57.6% males and 47.6% female having normal BMI. Most common factors associated with the presence of hypertension in our study population were "smoking", "use of ghee “and " lack of exercise". 22.5 percent of our male population smoke regularly and 39.5% female were in habit of using ghee daily. 95 (26.7%) hypertensive females and 61(21%) hypertensive males among our study population were having a family history of hypertension. Out of total type A population, 70(49.3%) were found to be hypertensive. Conclusion: In the present study, the frequency of hypertension in medical OPD patients was very high, (as 47 % of our study population was suffering from it). Most of the patients were in 41-50 years age group.